2021
DOI: 10.1007/s42729-021-00412-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Drought Stress in Sunflower (Helianthus annuus L.) Through Exogenous Application of β-Aminobutyric Acid

Abstract: Drought stress is a serious threat for sustainable crop production throughout the world especially in arid and semi-arid regions and one of the main constraints to sunflower (Helianthus annuus L.) production. Different mitigation strategies, including foliar spray of osmolytes such as β-aminobutyric acid (BABA), help the crop to combat drought conditions. A 2-year field study was conducted to evaluate the effect of exogenous application of BABA on the growth, productivity, and net return of sunflower under dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In addition, adverse effects imparted by DS depend on the intensity and duration of stress [15,16]. DS at critical growth stages, such as the seedling, vegetative or reproductive stages [17,18], leads to a severe reduction in relative water content and crop yield. Moreover, water deficit conditions at earlier growth stages when roots have not been fully developed results in stunted plant growth and a reduction in the binding of CO 2 [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adverse effects imparted by DS depend on the intensity and duration of stress [15,16]. DS at critical growth stages, such as the seedling, vegetative or reproductive stages [17,18], leads to a severe reduction in relative water content and crop yield. Moreover, water deficit conditions at earlier growth stages when roots have not been fully developed results in stunted plant growth and a reduction in the binding of CO 2 [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…After that, readings were recorded from a UV-vis spectrophotometer (V-73, Japan) at the wavelength of 410 nm. Further calculations were processed by the following Equation (2) [ 43 , 44 ]. where V is the final volume of plant/soil digested material after dilution (mL), V 1 is the volume of plant/soil digest used for P assessment purposes (mL), V 2 is the volume of flask used for assessment (mL), and Wt is the dry weight of plant/soil (g) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data of each parameter were taken in three replicates and shown as means ± standard error of the means (mean ± SEM). The significance of variables was assessed by analysis of variance (ANOVA) and means were ranked on Tukey’s HSD (honestly significant difference) test ( p ≤ 0.05) using Minitab ® Statistical Software (version: 20.3, USA) [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have also shown that elevated CO 2 causes a 20–30% increase in net assimilation rate, together with an increase in dry matter and yield of crops (Cruz et al, 2018; Pan et al, 2018; Xie et al, 2018). Rising levels of CO 2 , temperature and water‐deficit cause promising effects on plant growth and production, as the potential beneficial effects of elevated CO 2 include optimal growth yield in areas where drought currently causes crop failure (Shahzad et al, 2018; Wasaya et al, 2021). According to AbdElgawad et al (2015), elevated CO 2 has been shown to mitigate the stress impact of drought, and they quote examples of how the reduction in drought stress affects barley and alfalfa crops (Robredo et al, 2007; Zeid and Shedeed, 2006).…”
Section: Introductionmentioning
confidence: 99%